The Informal Structure of Senpai (Seniors), Kohai (Juniors), and Doki (Peers) in Japanese Organizations - Tomoki Sekiguchi; Megumi Ikeda (Encyclopedia)
In Japanese organizations, those who join earlier are called senpai (seniors), those who join later are kohai (juniors), and those who join in the same year are called doki (peers). The relationships among senpai, kohai, and doki function as an informal hierarchical structure working in tandem with the formal job-based organizational hierarchy. These relationships are deeply rooted in unique Japanese concepts, such as ba, the Confucian cultural tradition that influenced the formation of Japanese society, and the historical background of large organizations in modern Japan. Specifically, the seamless school-to-work transition due to the batch hiring of new graduates every April creates a similar hierarchical structure to that of senpai, kohai, and dokyusei (classmates) in schools. The balance between the formal job-based hierarchy and informal seniority-based (senpai–kohai–doki) hierarchy has been the base of the stable and harmonious organizational characteristics that enable effective knowledge management and efficient operations but poses challenges in adapting to new environments.